1989
DOI: 10.2135/cropsci1989.0011183x002900010024x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soybean to Air Temperature and Carbon Dioxide Concentration

Abstract: Documented increases in global atmospheric CO2 concentration have stimulated interest in the direct effects of CO2 on plant growth and yield as well as the interactive effects of CO2 with other major climatic variables. This study was conducted to determine the effects and interactions of CO2 concentration and air temperature on the development, growth, total nonstructural carbohydrate (TNC), and final seed yield of soybean [Glycine max (L.) Merr., cv. Bragg] grown season‐long in naturally lit, controlled‐envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
127
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(152 citation statements)
references
References 0 publications
20
127
2
1
Order By: Relevance
“…Our results on dry matter production in agreement with many previous studies on different crops showed increase in total dry matter production of soybean [38] [65]- [67], dry bean [43], peanut [68] 2 ] at later stage was attributed due to the partitioning of greater amounts of assimilated carbon towards the growing organs. Earlier studies also showed that the extra carbon fixed by the plants due to [CO 2 ] enrichment translocate to the growing axis [71].…”
Section: Effect Of Elevated Co 2 and Soil Moisture On Dry Matter Prodsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results on dry matter production in agreement with many previous studies on different crops showed increase in total dry matter production of soybean [38] [65]- [67], dry bean [43], peanut [68] 2 ] at later stage was attributed due to the partitioning of greater amounts of assimilated carbon towards the growing organs. Earlier studies also showed that the extra carbon fixed by the plants due to [CO 2 ] enrichment translocate to the growing axis [71].…”
Section: Effect Of Elevated Co 2 and Soil Moisture On Dry Matter Prodsupporting
confidence: 93%
“…This agrees many with the results of previous studies of [38] and [39] and contradicts the findings of [40] [29] and reported alterations both in physiology and growth and . Carbon dioxide (a) and soil moisture levels (b) on number of root nodules of soybean at 44DAP ( ** P < 0.014 and * P < 0.048 for CO 2 and soil moisture levels, respectively).…”
Section: Effect Of Elevated Co 2 On Phenologysupporting
confidence: 88%
“…A mean temperature range of [29][30][31] o C has been indicated as the optimum range for soybean vegetative growth (Ziska and Bunce, 1995;Setiyono et al, 2010), and the mean temperature of T2 and T3 were close to this range. Similarly, the main stem plastochron interval decreases and the final main stem node number increases in soybean with higher [CO 2 ] (660 μmolmol −1 ), accompanied by a rise in mean temperature between 22.5 and 32.5 °C (Baker et al (1989).…”
Section: Plant Height Branches and Racemes Distributionsmentioning
confidence: 99%
“…In contrast, reduced stomatal conductance and transpiration are additional reasons for the measured crop yield enhancement under water stress conditions. Because the upper optimum temperature of most soybean varieties ranges from 20 to 30°C (Baker et al, 1989), an increase in air temperature would also significantly limit production.…”
Section: Introductionmentioning
confidence: 99%